PENERAPAN NILAI-NILAI PANCASILA DALAM PENGHARMONISASIAN PERATURAN DAERAH - Nurfi Utami, Wiji; Setiadi, Wicipto (Jurnal Yuridis, 2024)
Regional regulations are the product of Regional Government legislation which must not conflict with higher regulations according to the hierarchy of statutory regulations and must not be outside the will of the Central Government. In the context of supervision by the Central Government, it is necessary to harmonize the Draft Regional Regulations. This research focuses on discussing the urgency of harmonizing Regional Regulations and the application of Pancasila values ​​in harmonizing Regional Regulations. The research method used is qualitative with a normative juridical approach and prescriptive characteristics. From the results of the study, it was found that the urgency of harmonizing regional regulations is summarized in 3 (three) reasons, namely first, because regional regulations are a sub-system in the national legal system and are in the hierarchy of statutory regulations. Second, regional regulations can be tested through the judicial review or executive review. Third, to ensure legal certainty in the process of forming regional regulations. In essence, the harmonization of regional regulations is based on the application of Pancasila values, this is carried out as a form of preventive effort to prevent overlapping legal products. Keywords : Pancasila, Harmonization, Regional Regulations.